Acetaminophen Mimics the Action of Salbutamol in Relaxing Gravid Human Uterus - In - Vitro - Hilmy, Mahdi I. (Journal of the Faculty of Medicine Baghdad, 2007)
Management of preterp'labour generally treated by salbutamol even with some expected disturbing -maternal pulmonary oedema , respiratory distress andcardiovascular side effects and neonatal low-sized and cellularity of thymus and lymph nodes. This demands finding a substitute free of these side effects . Initially, acetaminophen was tested on rats uterine horns and on pregnant rats and reported an effective relaxation of the uterine horns and profound delay in parturition . These results jestified an in-vitro study on strips of gravid human uterus ruptured during difficult labour. Acetaminophen (50 mg) reduced tension by 50% which was comparable decrease in tension when 5 gg of salbutamol was added. Profound drop in tension when adjunct use of both drugs, while repeated three doses of 50 mg acetoaminophen were added separately resulted in corresponding drops in tesion down to below resting level . These findings encouraged future clinical trials on threatened women with abortion since the use of acetaminophen in the usual dosage is effective tocolytic agent  without any maternal side effect but with mild possible neonatal lung congestion as a result of transient narrowing of ductus arteriosis especially in advanced gestation age.